Analisis Pengelolaan Sampah Dan Strategi Peningkatan Partisipasi Masyarakat Di Kelurahan Tuah karya - Fiona Deanovans Fiona; Dhiya Saffanah. H; Eva Indriyani; Fitri Oktavian Lubis; Haida Saqilia; Jodi Cristian; Hambali Hambali; Fitri Rahmatullaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to assess community based waste management at Bank Sampah Mutiara The Gade (Clean & Gold), located in Tuah Karya Subdistrict, Pekanbaru. The research employs a qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that Bank Sampah Mutiara The Gade (Clean & Gold) has successfully raised public awareness regarding waste management while simultaneously reducing unmanaged waste. Furthermore, the study identifies several key factors contributing to the program’s success, including active community participation, government support, and collaboration with the private sector.Bank Sampah Mutiara The Gade (Clean & Gold) serves as a successful model of community-based waste management and can be used as a reference for similar initiatives in other regions. The program emphasizes the importance of collaboration among government entities, private sector stakeholders, and educational institutions, supported by sustainable policy frameworks to ensure effective and enduring waste management practices.The study also highlights several challenges faced by Bank Sampah Mutiara The Gade (Clean & Gold), such as limited funding, varying levels of public awareness, and insufficient human resource capacity in waste management. Therefore, systematic reinforcement is needed through stable policy support, increased budget allocation, and the development of integrated management models.In conclusion, this research is expected to contribute to the advancement of more effective and sustainable community-based waste management in Indonesia. The findings may also serve as a valuable reference for policymakers and relevant stakeholders in designing improved waste management programs.